INTRODUCTION OF MULTILINGUAL TRAINING PROGRAM - Bissalieva, N.S.; Shibintaeva, A.A. (Западно-Казахстанский аграрно-технический университет имени Жангир хана, 2015)
The article considers the need for a policy of Kazakh President Nursultan Nazarbayev on the teaching of three langua ges. As well as the importance of learning the Kazakh, Russian and English languages in the preparation of the training of future specialists.Gives examples of policy implementation trinity languages on the example Zhangir Khan WKATU.
Keywords: multilingual; language; communication; program; culture; national; knowledge; foreign; integration